The effect of commercial herbal toothpastes on dental wear: a comparative evaluation by Optical coherence tomography (Research, Society and Development, 2021)
The purpose of this study was to compare the tooth wear in function of the use of different commercial herbal toothpastes through the analysis of Optical Coherence Tomography (OCT). Twenty bovine teeth were obtained and distributed in 4 groups (n = 5) according to the dentifrice used: G1: Captive Nature (Chamomile, Xylitol, Juá and Salvia); G2: Suavetex Content (Turmeric); G3: Colgate Triple Action (positive control); G4: distilled water (negative control). The samples were painted in the half of the fragment with nail polish so that only half of the fragment was brushed. The simulated brushing (20,000 cycles) was performed with linear movements, under static axial load of 200g and speed of 4.5 cycles per second. After this step, an analysis was performed through OCT and and the images obtained were evaluated to identify possible changes in the specimen surface. According to the qualitative analysis of the OCT images, enamel wear was not observed, since all measurements were null. Regarding the evaluation of dentin, surface wear was observed in all groups except G4, but G3 had the highest number of samples with surface wear around 21.32%. All dentifrices had abrasive wear on the dentin surface to a greater or lesser extent, but there was no wear on the enamel surface.